2021
DOI: 10.1039/d1ee02485j
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective electroreduction of N2 and CO2 to urea over artificial frustrated Lewis pairs

Abstract: Precisely fabricated frustrated Lewis pairs in the Ni3(BO3)2 nanocrystal achieve integration of the active sites and effective electrocatalytic C–N bond coupling to synthesize urea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
152
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 44 publications
1
152
0
Order By: Relevance
“…For the N 2 molecule, the specific electron transfer path is: σ orbitals (N 2 ) → empty d orbitals (Ti) and occupied d orbitals (Ti) → π* orbitals (N 2 ), which results in the polarization of N 2 molecules and elongation of the NN bond, and enhances the proton affinity to achieve the efficient activation of N 2 and the entire reduction processes. 7 In Fig. 3e, it is obviously observed that charge transfer is in the order of Ti 2 CO 2 (0.06 e ) < Ti 2 CF 2 (0.55 e ) < Ti 2 CH 2 (0.61 e ) < Ti 2 C(OH) 2 (1.07 e ), which is in accordance with the activation ability.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…For the N 2 molecule, the specific electron transfer path is: σ orbitals (N 2 ) → empty d orbitals (Ti) and occupied d orbitals (Ti) → π* orbitals (N 2 ), which results in the polarization of N 2 molecules and elongation of the NN bond, and enhances the proton affinity to achieve the efficient activation of N 2 and the entire reduction processes. 7 In Fig. 3e, it is obviously observed that charge transfer is in the order of Ti 2 CO 2 (0.06 e ) < Ti 2 CF 2 (0.55 e ) < Ti 2 CH 2 (0.61 e ) < Ti 2 C(OH) 2 (1.07 e ), which is in accordance with the activation ability.…”
Section: Resultssupporting
confidence: 64%
“…1,3 Therefore, development of effective, sustainable, and economically competitive approaches is urgently needed. Electrochemical methods are believed to be a green and sustainable alternative to the conventional Haber-Bosch method and have been successfully applied in hydrogen evol-ution reaction (HER), 4 oxygen evolution reaction (OER), 5 oxygen reduction reaction (ORR), 6 carbon dioxide reduction reaction (CO 2 RR), 7 and nitrogen reduction reaction (NRR). 8 Importantly, rational design and synthesis of electrocatalysts should open the door to highly efficient electrochemical transformation of these small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…5f). 4 For the distal pathway, the Δ G value for the transition from *NCONH to *NCONH 2 is 0.94 eV, which is higher than that of the alternating pathway (*NCONH → *NHCONH, 0.58 eV). The comparative results illustrate that urea electrosynthesis is prone to undergoing an alternating mechanism rather than a distal pathway for the production of urea molecules.…”
Section: Resultsmentioning
confidence: 87%
“…3 Compared with the harsh industrial synthesis process, an electrocatalytic approach (N 2 + CO 2 + 6H + + 6e − → CO(NH 2 ) 2 + H 2 O), which can be carried out under ambient conditions, provides an appealing route for realizing low-cost artificial CO 2 and N 2 fixation, however, the related activity and selectivity remain extremely low. 1 b ,4…”
Section: Introductionmentioning
confidence: 99%
“…In this section we encounter about the interesting electrocatalyst Ni3(BO3)2, 35 which shows flower like morphology shown in figure 3g. The electrochemical performance was brilliant and reports urea yield of 9.75 mmol h -1 g -1 and FE of 20.36% at -0.5 (vs. RHE).…”
Section: (D) Metal Boratesmentioning
confidence: 99%